1976
DOI: 10.1038/bjc.1976.183
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of low-dose pre-operative X-irradiation of implanted mouse mammary carcinomas on local recurrence and metastasis

Abstract: Summary.-Pre-operative X-irradiation of s.c. implanted first-generation mammary tumours in C3H mice, using either 500 rad or two fractions of 350 rad, produced no improvement in the success of surgery in causing local control or in reduction of distant metastases. The metastasis rate was just significantly higher after the twofraction treatment of the implanted tumour than after surgical removal alone. The results are in agreement with previously published results on carcinomas and a sarcoma but contrast with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…This difference might be due to fractionated irradiation and acquisition of radioresistance. Some studies have shown that reduced E-cadherin expression was correlated with a high incidence of cancer metastasis and invasion (Doki et al, 1993;Kadowaki et al, 1994), and radiation enhanced the ability to form metastases (Sheldon and Fowler, 1976). Our results also suggest that the tumour cells that acquired radioresistance may have higher invasive ability and metastatic potential.…”
Section: Genes Related To Cell Adhesion and Motilitysupporting
confidence: 68%
“…This difference might be due to fractionated irradiation and acquisition of radioresistance. Some studies have shown that reduced E-cadherin expression was correlated with a high incidence of cancer metastasis and invasion (Doki et al, 1993;Kadowaki et al, 1994), and radiation enhanced the ability to form metastases (Sheldon and Fowler, 1976). Our results also suggest that the tumour cells that acquired radioresistance may have higher invasive ability and metastatic potential.…”
Section: Genes Related To Cell Adhesion and Motilitysupporting
confidence: 68%
“…An epidemiological study investigated association of secondary malignancies in prostate cancer patients during the ten years after radiotherapy and found that these patients have a detectable increase in secondary malignancies in regions distant from the site of irradiation [48]. In some cases, these secondary malignancies could be attributed to other factors, such as pre-existence of micrometastasis, intrinsic radiosensitivity [49], or shedding of viable tumor cells from irradiated tumors [50; 51]. However, tumor- and/or treatment-induced oxidative stress and consequent genomic instability and secondary carcinogenesis could also contribute to second cancers.…”
Section: Radiation-induced Non-targeted Effectsmentioning
confidence: 99%
“…So far, no studies have proved that this effect impacts metastasis in patients, but certainly such an opportunity exists. Indeed, there are studies of metastasis in irradiated versus non-irradiated mice that point to this conclusion [17,18]. As addressed later in this review, such effects may interfere with assessing the prognostic powers of CTC count in patients, which should be taken into consideration.…”
Section: Ctc Mobilization By Treatmentmentioning
confidence: 97%